2008
DOI: 10.1590/s0100-204x2008001100008
|View full text |Cite
|
Sign up to set email alerts
|

Glifosato aplicado com diferentes concentrações de uréia ou sulfato de amônio para dessecação de plantas daninhas

Abstract: Resumo -Este trabalho foi desenvolvido com o objetivo de avaliar a efi cácia do herbicida glifosato, para a dessecação de trapoeraba (Commelina benghalensis) e outras plantas daninhas, quando combinado a diferentes concentrações de sulfato de amônio ou uréia. Foram conduzidos três experimentos com tratamentos semelhantes: dois em campo e um em casa de vegetação. Os tratamentos aplicados em campo foram: glifosato (360 g ha -1 de e.a.), isolado ou acrescido de quatro concentrações de sulfato de amônio (2,5, 5, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0
9

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 26 publications
1
5
0
9
Order By: Relevance
“…Another justification is based on the differential absorption of the molecule, which varies among species and may be related to the higher amount of wax in the leaf, cuticle thickness and metabolizing capacity presented by C. erecta (Santos et al, 2002;Carvalho et al, 2008;Xu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Another justification is based on the differential absorption of the molecule, which varies among species and may be related to the higher amount of wax in the leaf, cuticle thickness and metabolizing capacity presented by C. erecta (Santos et al, 2002;Carvalho et al, 2008;Xu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…O herbicida glyphosate reduziu a massa fresca e seca do capim-amargoso (Figura 2), sendo as variáveis adequadamente ajustadas ao modelo logístico proposto por Seefeldt et al (1995). Carvalho et al (2008Carvalho et al ( , 2009a ) ou em combinação com U promoveu controles mais baixos (Tabela 4).…”
Section: Resultsunclassified
“…Nesse sentido, a ureia tem sido utilizada em aplicações foliares como fonte de nitrogênio e, principalmente, como agente facilitador da penetração de nutrientes catiônicos, aniônicos e herbicidas (Yamada et al, 1965;Freire et al, 1981;Durigan, 1992). A adição de sulfato de amônio à calda de pulverização também tem sido associada à maior eficácia de herbicidas (Nalewaja & Matysiak, 1993;Pratt et al, 2003;Young et al, 2003;Carvalho et al, 2008Carvalho et al, , 2009a. Contudo, não foram encontrados trabalhos que avaliaram a adição concomitante de ureia e sulfato de amônio à calda de pulverização.…”
unclassified
See 1 more Smart Citation
“…Currently, the addition of nitrogen sources as adjuvant to herbicide is MATHEUS G. SILVA, ORIVALDO ARF and PAULO E. TEODORO being investigated. This practice has been linked to reduction of doses and better absorption and translocation of molecules, as evidenced by Carvalho et al (2008) and Ruas et al (2012), who concluded that the addition of urea to glyphosate increased the control of several weed species, decreasing its required dose.…”
Section: Introductionmentioning
confidence: 99%